2003
DOI: 10.4067/s0034-98872003000900002
|View full text |Cite
|
Sign up to set email alerts
|

Factores de riesgo de enfermedad cardiovascular en adultos jóvenes

Abstract: Background: A precise knowledge of the prevalence and importance of cardiovascular risk factors will facilitate the development of preventive strategies. Aim: To study cardiovascular risk factors among healthy young adults. Subjects and methods: Eight hundred and fifty subjects aged 22 to 28 years, living in two cities in Valparaiso province, were studied. Weight, height and blood pressure were recorded. A fasting blood sample was obtained from 806 individuals (54% female), to measure plasma lipids, glucose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
25

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 10 publications
2
6
0
25
Order By: Relevance
“…Tal consideração é feita do ponto de vista biológico do desenvolvimento humano, por serem esperadas nessa fase boas condições de saúde físicas e sensoriais, questão também culturalmente sustentada (12) . Referindo-se especialmente à saúde cardiovascular, alguns estudos evidenciaram o aparecimento de FRCV e DCV ainda na infân-cia (3)(4)6) , o que explicaria os crescentes números envolvendo a fase adulta jovem (5,14) . A raça foi autorreferida neste estudo e apontou para uma maioria de mestiços, que, se somada à porcentagem de negros, chega a 69,7%, e aponta prevalência de risco para hipertensão duas vezes maior em pessoas consideradas não brancas (10) .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Tal consideração é feita do ponto de vista biológico do desenvolvimento humano, por serem esperadas nessa fase boas condições de saúde físicas e sensoriais, questão também culturalmente sustentada (12) . Referindo-se especialmente à saúde cardiovascular, alguns estudos evidenciaram o aparecimento de FRCV e DCV ainda na infân-cia (3)(4)6) , o que explicaria os crescentes números envolvendo a fase adulta jovem (5,14) . A raça foi autorreferida neste estudo e apontou para uma maioria de mestiços, que, se somada à porcentagem de negros, chega a 69,7%, e aponta prevalência de risco para hipertensão duas vezes maior em pessoas consideradas não brancas (10) .…”
Section: Discussionunclassified
“…Essa situação tem contribuído para dois grandiosos e ainda crescentes problemas de saúde pública mundial: o sobrepeso e a obesidade (1) . Estudos têm demonstrado sua magnitude nas diversas fases do ciclo vital: na infância e adolescência (5) , entre adultos e idosos (10) . Esta pesquisa revelou 4% de adultos jovens classificados como obesos tipo 1 ou 2, que somados aos com sobrepeso chegam a 19,4% da amostra.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…24 Among German college students, it was found that more than 95% consumed less than fi ve servings of fruits and vegetables a day, 60% had inadequate physical activity and 31% were smokers. 13 Smoking prevalence in the sample studied was also lower than that found among young adults in Chile 5 and other Latin American countries. 23 This lower rate refl ects a trend of reduced smoking prevalence in Brazil resulting from successful anti-smoking public policies that have been implemented for the last 20 years.…”
Section: Discussionmentioning
confidence: 85%
“…Sin embargo, se debe destacar la validez internacional del IPAQ, lo que permite confiar en la reproducibilidad de los datos obtenidos. A pesar de que nuestra población era joven, nuestro estudio reveló una elevada prevalencia de FR y diferencias entre ambos sexos, lo que ya se había comunicado en una descripción preliminar de esta población 20 . Un hecho destacado, fue el diferente impacto de la AF por sexo actividad física y riesgo cardiovascular -a. arteaga et al sobre los FR.…”
Section: Discussionunclassified